“Nobody cares that these things are happening” – qualitative analysis of street harassment experiences: “Nobody cares that these things are happening” – qualitative analysis of street harassment experiences (Archives of Criminology, 2026)
Street harassment constitutes the most prevalent form of sexual violence experienced by women and girls, occurring across diverse sociocultural contexts, including in Poland. Although this phenomenon affects two-thirds of women and one third of men, its routine manifestations are still trivialised (as harmless hassling) or romanticised (as a form of flirting). This article aims to fill a gap in the Polish literature with an in-depth analysis of the subjective experiences of street harassment victims and an examination of reactions to these violations. An analysis of 26 qualitative interviews indicates that street harassment restricts women’s freedom of movement in public spaces, forcing them to negotiate for their safety at the expense of their sense of freedom. The indifference of peers and relatives as well as evidentiary difficulties, perpetuate the belief that such behaviour is socially accepted, reinforcing the victims’ sense of helplessness.